Current understanding and treatment of gliomas - Raizer, Jeffrey J.; Parsa, Andrew (Cancer treatment and research, 2015)
This book reviews the significant advances in our understanding of glioma biology that have been achieved during the past decade and describes in detail the resultant new approaches to treatment. Improvements in surgical techniques, radiation therapy, and chemotherapy are comprehensively covered, with discussion of their impact in decreasing patient morbidity and increasing survival. In addition, individual chapters are devoted specifically to current treatment for low-grade gliomas, anaplastic gliomas, and glioblastoma multiforme. Other topics addressed include treatment of the elderly patient, investigating emerging therapies from small molecules to immunotherapy and palliative care. This timely book will be a valuable source of up-to-date information for practitioners and will also be of interest to researchers